Social partnerships in vocational training : building community capacity - Seddon, Terri [Verfasser]; Billett, Stephen [Verfasser] (NCVER, 2004)
The aim of this project was to examine the nature of social partnerships and how they may be relevant to the vocational education and training (VET) sector. Vocational education and training, which supports industry, individuals and communities, is increasingly identified as an important means of strengthening local communities. This relatively recent role for the VET sector complements its long-standing role in the development of skills and attitudes necessary for work. This sector also offers ‘second chance’ opportunities to those who had been unsuccessful at school or university. (Editor, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; I 2.3.5 Australien, Ozeanien; Sozialpartnerschaft; Berufsbildung; Australien; Bundesrepublik Deutschland